1998
DOI: 10.1046/j.1432-1327.1998.2550139.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of melanogenesis inhibition by tumor necrosis factor‐α in B16/F10 mouse melanoma cells

Abstract: The inflammatory cytokine tumor necrosis factor-A (TNF-A) is present in the dermal and epidermal layers of normal skin [Kilgus, O., Payer, E., Schreiber, S., Elbe, A., Strohal, R. & Stingl, G. (1993) J. Invest. Dermatol. 100, 674Ϫ680]. Its local concentrations are modified by several stimuli, including wound healing and ultraviolet irradiation. Moreover, TNF-A inhibits melanogenesis in normal melanocytes [Swope, V., Abdel-Malek, Z., Kassem, L. & Norlund, J. (1991) J. Invest. Dermatol. 96, 180Ϫ 185], and is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 13 publications
5
61
0
1
Order By: Relevance
“…Despite its inhibitory activity, the minimal level of ZAG is also required for melanin synthesis. As previously reported, tumor necrosis factor-a also inhibits melanin synthesis by human primary melanoma and B16 melanoma cells (137,138), but ZAG inhibits melanin synthesis by B16 cells via a tumor necrosis factor -independent mechanism. ZAG is produced by normal epidermal keratinocytes, where its expression increases with cellular differentiation (29).…”
Section: Regulation Of Melanin Productionsupporting
confidence: 77%
“…Despite its inhibitory activity, the minimal level of ZAG is also required for melanin synthesis. As previously reported, tumor necrosis factor-a also inhibits melanin synthesis by human primary melanoma and B16 melanoma cells (137,138), but ZAG inhibits melanin synthesis by B16 cells via a tumor necrosis factor -independent mechanism. ZAG is produced by normal epidermal keratinocytes, where its expression increases with cellular differentiation (29).…”
Section: Regulation Of Melanin Productionsupporting
confidence: 77%
“…In vitro direct analyses of skin T cells from the margins of vitiliginous skin have shown that polarized type-1 T cells (CD4+ and CD8+), which secrete predominantly TNF-a and interferon-g, are associated with the destruction of melanocytes during active vitiligo (Huang et al, 2002;Wankowicz-Kalinska et al, 2003). In addition to causing apoptosis of melanocytes, TNF-α also inhibits melanocytogenesis through an inhibitory effect on tyrosinase and tyrosinase-related protein (Martínez-Esparza et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of Tyrosinase Activity Tyrosinase activity was measured using the method of Martinez-Esparza et al 20) Cells were pretreated with 1-30 mM of 3 compounds for 72 h. The cells were then washed twice with ice-cold PBS and lysed in lysis buffer (80 mM PO 4 bufferϩ1% Triton X-100ϩ100 mg/ml phenylmethanesulphonylfluoride (PMSF)) for 2 h in a deep freezer. Lysates were centrifuged at 12500 rpm for 15 min to remove insoluble material.…”
Section: Measurement Of Melanin Contentmentioning
confidence: 99%